The Linguistic Landscape of Pentingsari Tourism Village in Yogyakarta: Code Switching and Multilingualism - Rastitiati, Ni Kade Juli; Ariasri, Nyoman Reni; Arjaya, I Ketut; Suprastayasa, I Gusti Ngurah Agung (LACULTOUR: Journal of Language and Cultural Tourism, 2024)
The linguistic landscape, defined as the visibility and representation of languages in public spaces, mirrors societal multilingualism and cultural dynamics. This study delves into the intricate interplay of language and society within the tourism village landscape of Pentingsari in Yogyakarta. It employed qualitative methods, including ethnographic observation, document analysis, and interviews, to decipher the layers of meaning embedded in the linguistic landscape. Ethnographic observation involves systematic documentation of linguistic elements encountered in public spaces, including signs, advertisements, and graffiti. Document analysis further scrutinized these linguistic artefacts' textual and visual features, identifying patterns and themes within the linguistic landscape of the village. It found that the linguistic landscape of Pentingsari Tourism Village was characterized by multilingual and codeswitching phenomena, evidenced by the utilization of various languages, including Indonesian, Javanese, Arabic, and English. In addition, it also showed that the phenomena were not primarily due to its status as a tourism village, but rather, it served the needs of the local community.